2006
DOI: 10.1016/j.physc.2005.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Methods of introduction of MgO nanoparticles into Bi-2212/Ag tapes

Abstract: The effect of addition of ultra-fine MgO particles, obtained by Mg combustion, in Bi-2212/Ag tapes was investigated. Bi-2212/Ag tapes were prepared by coating and partial melt processing. Four different methods of MgO particles embedment were applied in green tape preparation; settlement of MgO in Bi-2212, pre-mixing of MgO in the solvent, deposition of the MgO into the solvent, and deposition of MgO onto the surface of Bi-2212. Microstructural studies of processed tapes show that uniformity of MgO particles d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
30
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 16 publications
0
30
0
Order By: Relevance
“…Ultra fine MgO nanoparticles were added to enhance the superconducting properties of Bi-2212/Ag tapes [14]. The effect of Al 2 O 3 nanoparticles on superconducting properties of YBa 2 Cu 3 O 7-δ was investigated and reduction in T c was observed, which was attributed to the insulating nature of these nanoparticles [15].…”
Section: Introductionmentioning
confidence: 99%
“…Ultra fine MgO nanoparticles were added to enhance the superconducting properties of Bi-2212/Ag tapes [14]. The effect of Al 2 O 3 nanoparticles on superconducting properties of YBa 2 Cu 3 O 7-δ was investigated and reduction in T c was observed, which was attributed to the insulating nature of these nanoparticles [15].…”
Section: Introductionmentioning
confidence: 99%
“…In our previous works, we have investigated the effect of addition of ultra-fine MgO particles on the microstructure and superconducting properties of Bi-2212/Ag tapes, prepared by a dip-coating and partial melting process [11,12]. It was found that significant enhancement in the magnetization hysteresis below the transition temperature could be achieved if ultra-fine MgO particles are individually dispersed in the Bi-2212 matrix [11].…”
Section: Introductionmentioning
confidence: 99%
“…On this basis, a number of procedures for the introduction of ultra-fine particles of MgO into the Bi-2212 matrix have been developed and used in order to obtain a uniform distribution throughout the Bi-2212 matrix and conserve them as individual particles [12]. It was found that significant enhancements in magnetization hysteresis could be achieved in tapes produced by the settlement method as well as the solvent deposit/mixing method (details are presented in Section 2), both providing sufficient uniformity of the flux pinning centers' distribution.…”
Section: Introductionmentioning
confidence: 99%
“…Other techniques have been used during the sample preparation by changing the heat treatment where good quality samples might be obtained to carry high currents [6,7]. Introducing nano-particles in bulk superconductors has been also used to increase the pinning forces [8,9] and thus to enhance J c . Although great progress has been made to prepare HTSCs with high critical current density, some key problems are still unsolved so far.…”
Section: Introductionmentioning
confidence: 99%